Use of Generative AI by small-scale Farmers in Nigeria: An Empirical Study - SHITU, ADENIPEKUN; ANAFI , SURAJUDEEN; Tulagha, Ifiemi; Nain, Manjeet Singh; OJOBOLA, FOLASHADE; OLANIYAN, OMOTAYO; ALABI, OLAJUMOKE; AYEGBUSI, OLABISI; BAMIGBOYE, OLUWASEUN; OLATUNJI, COMFORT; FANU, ABIMBOLA; AYOTUNDE, KOLAWOLE; et al. (Indian Journal of Extension Education, 2025)
The study, conducted in 2025, investigated the digital readiness and use of generative artificial intelligence (AI) among small-scale farmers in Nigeria. A multi-stage sampling technique was used to select 120 small-scale farmers, and data were collected through interview schedules. The majority (62.5%) were small-scale farmers with over ten years of farming experience. Many of the small-scale farmers had digital access as a lot of them owned smart phones (64.2%) had internet connectivity (65%), and regularly used the internet (53.3%). Traditional media (Radio and TV) (63.3%) remained their primary source of agricultural information. Extension service access (4.2%) was notably low. Many small-scale farmers (64.2%) had used generative AI, mainly for accessing information (45%) and conducting basic research about their farm operations and general well-being (17.5%), and most indicated willingness to continue its use (89.2%). However, major barriers to the use of generative AI included limited awareness and lack of access to digital devices. AI awareness was generally low but positively associated with education. Although generative AI adoption is growing, significant challenges remain, underscoring the need for targeted generative AI training in agriculture as well as the design and implementation of more generative AI awareness program.